The rise of the Catholic Alt‐Right. (19th February 2020) - Wetzel, Dominic
Abstract: This paper examines the rise of the Catholic Alt‐Right, in particular the group Church Militant. Drawing on ethnographic research at a recent Catholic Men's Conference in a Midwestern battleground state it examines the manipulative integration of rightwing themes of anti‐feminism, anti‐LGBTQ community, anti‐immigration and anti‐leftist ideology into Catholicism. It maps the roots of the Catholic Alt‐Right out of prolife anti‐feminism, apocalyptic Marianism, the charismatic masculinity manual, and the flourishing of ultra‐conservative sects within Catholicism after the Vatican shutdown of liberation theology, feminist theology and the LGBT rights movement within the church in the 1980s and 1990s. It concludes with a re‐imagining of potential paths back to liberation.